A new species of Sidera (Hymenochaetales, Basidiomycota) from tropical Asia - Du, Rui; Wang, Li; Zhou, Meng; Chen, Jiajia (Phytotaxa, 2019)
A new poroid wood- rotting fungus, Sidera vesiculosa, is described from Singapore based on morphological characters and phylogenetic analysis. The species is characterized by annual, resupinate and waxy fresh basidiocarps, small pores measuring 7–9 per mm, a monomitic hyphal system with vesicular cells, the presence of rosette-like crystals, allantoid to lunate basidiospores measuring 2.9–3.7 × 0.6–1.0 μm, and causing a white rot. Phylogenetic analysis inferred from ITS and nLSU sequences indicates that the new species forms a distinct lineage with strong support and is closely related to Sidera lowei.